Modern views on the pathogenesis of hard dental tissues and periodontium lesions and means of their treatment in children with chronic diseases of the gastrointestinal tract. - Krupey, V. Y. (Medicni Perspektivi, 2014)
Changes in the mouth covity often reflect regularities of pathogenesis of a number of disease states, and primarily from the digestive tract. Therefore, the purpose of the study was to clarify pathogenesis of certain lesions of hard dental tissues and periodontal tissues in children with chronic diseases of the gastrointestinal tract and development of schemes for their treatment. The study observed 441 children aged from 7 to 15 years with dental caries and generalized chronic catarrhal gingivitis on the background of chronic gastritis and duodenitis, duodenal ulcer and malabsorption syndrome. All the children were divided into 2 groups - basic and comparison one. The study identified the most dangerous and little-known way of pathogenesis, which passes through the general processes of reducing the production of various proteins (immune system and antiseptics), is a violation of the general and local resistance and, ultimately, mineral metabolism. Such disorders impair complete mineralization of tooth enamel, reduce optimal composition and properties of saliva stimulating glycolysis processes in oral cavity. Prevention of dental caries and generalized chronic catarrhal gingivitis in children with chronic pathology of the gastrointestinal tract is based on the use of developed therapeutic and prophylactic complex, which includes mucosal gel Kvertulin, probiotic Latsidofil and drug Calcium D.